Identification of a master regulator Msd1 that governs meiotic entry in a global basidiomycete pathogen - Fanglin Zheng; Yanli Cao; Huiting Chen; Lili Yan; Feng Lv; Yuan Huang; Man Chen; Lin Su; Zhuozhuo Liu; Ye Huang; Tuyetnhu Pham; Xinping Xu; et al. (Proceedings of the National Academy of Sciences, 2026)
Meiosis is a hallmark of sexual reproduction. Although the core meiotic machinery is evolutionarily conserved from unicellular yeasts to Metazoan, the key regulators responsible for initiating meiosis vary across species and remain largely unidentified in major eukaryotic lineages, including the major phylum Basidiomycota in the Kingdom Fungi. The basidiomycete fungus Cryptococcus neoformans is a critical pathogen listed by the World Health Organization that causes life-threatening meningoencephalitis worldwide. Meiosis not only indirectly facilitates cryptococcal pathogenicity through generating genetically diverse spores but also directly contributes to host adaptation and disease progression. Here, we identified a novel transcription factor Msd1 that is responsible for activating meiosis in C. neoformans . Deletion of MSD1 impaired multiple sexual development events and strikingly abolished meiosis and subsequent sporogenesis (gametogenesis). Conversely, overexpression of MSD1 alone is sufficient to drive meiosis and the formation of meiotic spores, even in the absence of the external mating-inducing cues or when the mating pathway is genetically inactivated. Mechanistically, we demonstrated that Msd1 initiates meiotic entry by targeting two interconnected pathways. First, Msd1 activates the transcription of multiple evolutionarily conserved core meiosis-specific genes such as meiotic recombinase Dmc1. Second, Msd1 activates two RNA-binding proteins, Csa1 and Csa2, which ensure spatiotemporal expression of the aforementioned meiosis-specific genes to drive meiosis and sporogenesis. Collectively, our findings demonstrate that meiosis and the sequential sexual development events are spatiotemporally orchestrated by the master regulator Msd1, and is the first reported regulator initiating meiotic entry in a basidiomycete fungus.